Curriculum Development Of Leading Programs In Realizing The Potential And Character Of Students At Madrasah Aliyah - M. Hanif Satria Budi (JIEMAN: Journal of Islamic Educational Management, 2023)
In improving the quality of education, the curriculum of superior programs in madrasahs also contributes to producing quality graduates on a national scale. This is also a form of concern for educational institutions in dealing with weak human resources and morale of students in educational institutions. For this reason, the entire potential of education must be directed to achieve a progressive level of quality educational development, both quantitatively and qualitatively. This research method is qualitative using descriptive methods. The result of this research is the existence of a superior program curriculum, including 1) acceleration of tahfidz; learners can memorize the Qur'an in a school and cottage environment quickly and precisely, 2) acceleration of English; learners can fully complete the English material from basic to proficient so that in communication and language strictures dare to compete, 3) acceleration of the yellow book; students as students can easily learn and understand the classic books of salaf scholars, so that school graduates can fill out the taklim majlis or continue to a higher level at the Islamic boarding school.   Dalam meningkatkan kualitas pendidikan, kurikulum program unggulan yang ada di madrasah turut andil untuk mencetak lulusan yang berkualitas dalam skala nasional. Hal ini juga sebagai bentuk kepedulian lembaga pendidikan dalam menangani lemahnya sumber daya manusia dan moral peserta didik yang ada di lembaga pendidikan. Untuk itu, seluruh potensi pendidikan harus diarahkan untuk mencapai tingkat perkembangan pendidikan yang berkualitas secara progresif, baik secara kuantitatif maupun kualitatif. Metode penelitian ini adalah kualitatif dengan menggunakan metode deskriptif. Hasil dari penelitian ini adalah adanya kurikulum program unggulan antara lain 1) akselerasi tahfidz; peserta didik dapat menghafalkan Al-Qur’an dalam lingkungan sekolah dan pondok dengan cepat dan tepat, 2) akselerasi bahasa inggris; peserta didik dapat dengan lengkap materi bahasa inggris dari dasar hingga mahir sehingga dalam komunikasi dan ketata bahasaan berani bersaing, 3) akselerasi kitab kuning; peserta didik sebagai santri dapat dengan mudah mempelajari dan memahami kitab-kitab klasik ulama salaf,, sehingga lulusan sekolah sudah bisa mengisi majlis taklim atau melanjutkan ke jenjang yang lebih tinggi lagi di pondok pesantren.